Pengaruh Komitmen Organisasi terhadap Perilaku Organizational Citizenship - Bramanttyo Nurul Falah; TB. Zulrizka Iskandar; Sri Rahayu Astuti (Jurnal Ilmiah Psikologi MIND SET, 2018)
The purpose of this study is to examine the influence of organizational commitment on organizational citizenship behavior. Concepts of Meyer’s & Allen’s (1997) three components model of organizational commitment and Organ’s etc (2006) organizational citizenship behavior theory is used in this research. Using survey method, data was gathered toward 30 PT X organization’s members. The result showed that only affective commitment has significant positive influence toward organizational citizenship behavior, whereas continuance and normative commitment don’t have significant influence toward organizational citizenship behavior.